2022
DOI: 10.1038/s41598-022-09934-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single intra-articular administration of stanozolol in a naturally occurring canine osteoarthritis model: a randomised trial

Abstract: Osteoarthritis (OA) is a disease with a high negative impact on patient’s quality of life and a high financial burden. It is a source of chronic pain and affects all mammals, including humans and dogs. As the dog is a common model for translation research of human OA, and exploring spontaneous dog OA can improve the health and well-being of both humans and dogs. To describe the effect of the intra-articular administration of stanozolol in a naturally occurring canine OA model, forty canine (N = 40) hip joints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…Since the LOAD and the COI are a part of the routine follow-up for this population of dogs, and all fields are mandatory in the follow-up, we obtained results for both CROMs in all patients. The baseline values for the LOAD and COI were similar to the ones previously published for police working dogs with OA [24][25][26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 85%
“…Since the LOAD and the COI are a part of the routine follow-up for this population of dogs, and all fields are mandatory in the follow-up, we obtained results for both CROMs in all patients. The baseline values for the LOAD and COI were similar to the ones previously published for police working dogs with OA [24][25][26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 85%
“…The study demonstrated that the administration of stanozolol injections has yielded promising improvements in both pain management and quality of life outcomes in dogs with degenerative joint disease (DJD). Clinical studies in dog and other species have reported significant reductions in pain scores and enhanced mobility following stanozolol treatment [2,36,[49][50][51][52]. Additionally, tutors often observe improvements in their pets' activity levels and overall well-being, indicating a positive impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative joint disease (DJD), also known as osteoarthritis, is a common and debilitating condition characterized by progressive deterioration of articular cartilage, subchondral bone changes, and synovial inflammation. DJD primarily affects weight-bearing joints such as the hips, knees, and elbows, leading to pain, stiffness, and decreased mobility [1][2][3][4][5]. Brown's original survey, the Canine Brief Pain Inventory (CBPI), developed in 2006 at the University of Pennsylvania, School of Veterinary Medicine, stands as a pivotal tool in assessing pain in dogs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of multiple therapeutic approaches to the management of OA illustrates the challenges of successfully treating the disease. The treatment can include intra-articular modalities [ 5 , 6 , 7 , 8 , 9 ], photobiomodulation [ 10 ], oral joint supplements [ 11 ], mesotherapy [ 12 ], biological products [ 13 , 14 , 15 ], or others.…”
Section: Introductionmentioning
confidence: 99%